2014
DOI: 10.1111/hpb.12274
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of complications following intraoperative radiofrequency ablation for liver metastases

Abstract: Mortality and morbidity after IRFA, with or without resection, are low. Nevertheless, long interventions and concurrent bowel operations increase the risk for septic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Potential septic surgery is also known to cause higher post-operative complications. 13,28,30 As often in extensive surgeries, PVO was correlated with higher post-operative complications. In the literature, PVO seems to improve liver volume and function, 33 but is associated with more post-operative complications (blood loss) and may stimulate the growth of the remaining metastases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Potential septic surgery is also known to cause higher post-operative complications. 13,28,30 As often in extensive surgeries, PVO was correlated with higher post-operative complications. In the literature, PVO seems to improve liver volume and function, 33 but is associated with more post-operative complications (blood loss) and may stimulate the growth of the remaining metastases.…”
Section: Discussionmentioning
confidence: 94%
“…After 10 years and many studies, results are still heterogeneous, including patients with different and incomparable chemotherapies, without essential and exhaustive histological analysis. 10,1217 Our study is interesting as the patients received only one line of chemotherapy, giving us pertinent and homogeneous results on the impact of chemotherapy on liver. The study by Rubbia-Brandt et al 9 did not show any impact of sex, contrary to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Other reports concerning CRLM patients indicated that local control and oncological safety of ablative techniques were similar to liver resection. [34][35][36][37] Some reports indicate that combined resection and ablation achieves results comparable to conventional liver resection with respect to short-term postoperative outcomes and oncological outcomes. [38][39][40][41][42] However, oncological safety of combined resection and ablation is still under debate as multicenter randomized studies are lacking and contrasting results have been published before.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is a safe, economical, efficient transdermal technology in the treatment of patients with primary and secondary tumors, as well as unresectable tumors in the spinal canal and those that are insensitive to chemotherapy and radiotherapy (30,31). It can prevent or delay tumor progression and the risk of fracture, thus preventing or delaying paraplegia, reducing the pain caused by the tumor, and improving the daily activities and life quality of patients.…”
Section: Discussionmentioning
confidence: 99%